Analisis Turnover Intention Pada Karyawan Bagian Procurement Pt X Dengan Masa Kerja Di Bawah 2 Tahun - Sidiq, M Iqbal; Henry Pasaribu, Lamhot (Riviera Publishing, 2025)
Based on internal data, the turnover rate in the procurement division reached 35%, far exceeding other divisions in the company. This phenomenon is thought to be triggered by high work stress, low job satisfaction, and weak organizational commitment. These three factors directly or indirectly impact productivity, increase recruitment costs, and decrease the stability of the company's operations. This study aims to analyze the effect of work stress, job satisfaction, and organizational commitment on turnover intention in employees of the procurement division of PT X who have a work period of less than two years. The approach used in this study is quantitative with a causal-comparative method. Data were collected by distributing closed questionnaires based on a Likert scale to 40 employees who were the research samples. Data analysis was conducted through instrument validity and reliability tests, as well as multiple linear regression analysis supported by classical assumption tests including normality, multicollinearity, and heteroscedasticity tests. The results showed that work stress had a positive and significant effect on turnover intention (? = 0.330; p <0.01), which means that the higher the level of work stress, the greater the employee's intention to leave the company. Conversely, job satisfaction had a negative and significant effect on turnover intention (? = -0.189; p = 0.024), indicating that dissatisfaction with aspects such as compensation and work environment were triggers for the desire to resign. Organizational commitment was found to have the strongest negative effect on turnover intention (? = -0.372; p <0.01), confirming that employees with high emotional ties and involvement in the company tend to have greater loyalty. The managerial implications of these findings are the need to implement stress management programs such as job rotation and training, increasing job satisfaction through evaluation of compensation systems and career development opportunities, and strengthening organizational commitment through mentoring programs and employer branding strategies. This study provides an important contribution in formulating a more effective retention strategy for PT X.